2019
DOI: 10.1371/journal.pone.0223328
|View full text |Cite
|
Sign up to set email alerts
|

Surgical referral systems in low- and middle-income countries: A review of the evidence

Abstract: BackgroundReferral networks are critical in the timely delivery of surgical care, particularly for populations residing in rural areas who have limited access to specialist services. However, in low- and middle-income countries (LMICs) referral networks are often undermined by systemic inefficiencies. If equitable access to essential surgical services is to be achieved, sound evidence is needed to ensure efficient patient care pathways. The aim of this scoping review was to investigate current knowledge regard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
61
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(65 citation statements)
references
References 33 publications
3
61
0
1
Order By: Relevance
“…Comparing to the few other existing prehospital referral systems in Africa, NEMS' strengths lie in the presence of extensive SOPs, well-established communication flow, structured data collection system, and continuing education programs. 24,25 In this manuscript, the design and implementation phases of NEMS are described, a process that was not exempt from challenges, including lack of experience of local staff, paucity of information related to existing health care facilities, and poor condition of available vehicles. Moreover, problems had to be tackled related to the development of a brand new EMS from scratch, that needed to be properly integrated in the current National Health System and widely accepted by a population that experienced the stigma and fear associated with ambulances during the ravaging Ebola epidemic.…”
Section: Discussionmentioning
confidence: 99%
“…Comparing to the few other existing prehospital referral systems in Africa, NEMS' strengths lie in the presence of extensive SOPs, well-established communication flow, structured data collection system, and continuing education programs. 24,25 In this manuscript, the design and implementation phases of NEMS are described, a process that was not exempt from challenges, including lack of experience of local staff, paucity of information related to existing health care facilities, and poor condition of available vehicles. Moreover, problems had to be tackled related to the development of a brand new EMS from scratch, that needed to be properly integrated in the current National Health System and widely accepted by a population that experienced the stigma and fear associated with ambulances during the ravaging Ebola epidemic.…”
Section: Discussionmentioning
confidence: 99%
“…The quality and efficiency in referral systems in Lower and Middle Income Countries (LMIC) are often undermined due to system-related inefficiencies such as poor infrastructure, relevant materials/equipment and insufficient skilled human resource [ 9 ]. Despite having established superior services, the inefficiencies in referral methods of health systems in high–income countries are more pronounced [ 10 ] and the problem of long waiting times for elective surgeries more explicit in developed health systems. Delays in patients receiving specialised care due to inefficiencies in referral methods are purely a systems issue and could be resolved with streamlining the care pathways [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…A more recent systematic review of guidelines for elective referrals of adult patients to surgical specialists concluded that these improve the appropriateness of care [ 28 ]. However, a more up-to-date review is needed to help healthcare systems develop comprehensive protocols to establish effective and efficient referral systems in surgical care pathways [ 10 ]. To bridge the evidence gap in existing literature, this comprehensive systematic review will synthesise global evidence on policy strategies with a unique insight to effective primary care referral methods.…”
Section: Introductionmentioning
confidence: 99%
“…A more recent systematic review of guidelines for elective referrals of adult patients to surgical specialists concluded that these improve the appropriateness of care (25). However, a more up-to-date review is needed to help healthcare systems develop comprehensive protocols to establish effective and e cient referral systems in surgical care pathways (26). The objective of this paper, therefore, is to review and summarise recent research evidence relevant to primary care referral methods as part of the surgical care pathways that aimed to shorten waiting time for elective surgeries in adult patients.…”
Section: Introductionmentioning
confidence: 99%